Parkinson's Disease: Is It a Toxic Syndrome? - Seham A. Gad ELhak; Abdel Aziz A. Ghanem; Hassan AbdelGhaffar; Sahar El Dakroury; Mohamed M. Salama (Neurology Research International)
Parkinson's disease (PD) is one of the neurodegenerative diseases which we can by certainty identify its pathology, however, this confidence disappeares when talking about the cause. A long history of trials, suggestions, and theories tried linking PD to a specific causation. In this paper, a new suggestion is trying to find its way, could it be toxicology? Can we—in the future—look to PD as an occupational disease, in fact, many clues point to the possible toxic responsibility—either total or partial—in causing this disease. Searching for possible toxic causes for PD would help in designing perfect toxic models in animals.